Estoque de carbono e diversidade microbiológica em solos sob diferentes manejos nos biomas do Mato Grosso do Sul - NATIELLY PEREIRA DA SILVA (2024)
Carbon stock and microbiological diversity are intrinsically linked to land use and the biome. Mato Grosso do Sul's main land uses and occupation are: agriculture, pasture, eucalyptus planting and native vegetation. This State has a challenging goal of becoming carbon neutral by 2030. In view of the above, the hypothesis of this work is that land use and occupation influences the carbon stock and the microbiological biological diversity of the soil in different biomes in the state of Mato Grosso do Sul. This dissertation was separated into two chapters. In the first, the objective of this work was to evaluate the carbon stock at three depths in the main uses and occupation of soil in the Cerrado, Pantanal and Atlantic Forest biomes of Mato Grosso do Sul. In this work, different land uses were evaluated in each biome of MS, They are: agriculture, pasture, eucalyptus and native forest. Carbon stock assessments were carried out through the analysis of total soil carbon, soil density in the sampled soil layers (0-10, 10-20 and 20-40 cm) in 100 sampling points for each land use and occupation. and biome. The soil samples were grouped into a composite sample for each use and biome considering the two initial depths for soil microbiological identification analysis. Bacteria and fungi were identified using the 16S rRNA and ITS1/ITS2 PCR method, respectively. The results found demonstrate that the Cerrado has a greater carbon stock in the uses and occupations of eucalyptus, pasture and soybeans at a depth of 20-40 cm, while the native forest has a similar carbon stock in the Cerrado and Pantanal biomes. The lowest carbon stock was observed in the Atlantic Forest biome, when soybean was used and occupied at depths of 0-10 and 20-40 cm. The greatest diversity of bacteria was observed in the use of eucalyptus and pasture and in the Pantanal and Atlantic Forest biomes. The greatest diversity of fungi was observed in the use of pasture and soybeans and in the Cerrado and Atlantic Forest biomes. The results reported in this research can be used to outline public policy strategies for carbon absorption in the main uses and occupation of land in all biomes of Mato Grosso do Sul. Keywords: RNA. Agriculture. Cerrado. Mata-Atlântica. Pantanal.